Kesadaran dan Transformasi Model Pendidikan Pranikah Masyarakat Madura melalui Tradisi Ngabula - Mutiatus Soleha; Harto Wicaksono (Universitas Hamzanwadi, 2026)
Early marriage within the Madurese community, particularly in Bendungan Hamlet, is a social practice shaped by matchmaking traditions, religious beliefs, and deeply rooted cultural norms. This practice is often carried out at a young age and may lead to psychological, social, and marital challenges when prospective spouses lack sufficient preparation. This study aims to examine premarital education awareness among the Madurese community, the implementation of premarital education through the ngabula tradition from an Islamic perspective, and the transformation of premarital education models in contemporary society. The research adopts a qualitative narrative approach, employing observation, semi-structured interviews, and documentation as data collection techniques. Ten informants were selected using a snowball sampling method, consisting of religious leaders, female ngabula participants, early-married couples, and community members. Data were analyzed through thematic analysis and interpreted using Paulo Freire’s theory of consciousness alongside Arnold van Gennep’s rites of passage framework. The findings indicate that premarital education awareness develops across three levels of consciousness: magical, naive, and critical. The ngabula tradition functions as a form of non-formal premarital education that contributes to the development of mental, social, moral, and religious readiness among prospective spouses, particularly women. Furthermore, the ngabula tradition has undergone transformations in terms of practice and meaning while continuing to preserve its religious and cultural values. These values play an important role in supporting the formation of sakinah, mawaddah, and warahmah families within the Madurese social context.